Optimization of Destana policies (Resilience Disaster Village) to improve community preparedness for flood disaster in Bojonegoro District, Indonesia - Ningtyas, Trimurti; Larasati, Endang; Warsono, Hardi; Purnaweni, Hartuti (Management and Entrepreneurship: Trends of Development, 2021)
Natural disasters are one of the impacts on environmental dynamics, both natural and as a result of human behavior. The Destana (Disaster Resilient Village) policy is one of the programs created by BNPB (National Disaster Management Agency) and implemented by BPBD (Regional Disaster Management Agency) as one of the government’s efforts in dealing with disaster problems. The purpose of the study is to describe how Destana plays an optimal role in increasing community preparedness in dealing with floods. Using a qualitative approach, this study conducted observations on 11 Destana in Bojonegoro, conducted interviews with BPBD and each Destana coordinator and documented the activities Destana had carried out to improve community preparedness. The first finding in the implementation of Destana is a medium for the community together with stakeholders in disaster management to carry out activities related to increasing community knowledge about flood preparedness. The second result is that through Destana the community becomes more aware of its environment and has a responsibility to protect itself. Finally, there is a pattern of optimizing the use of rural resources to be used in every Destana activity. The three results indicate that Destana has been used and is running optimally in an effort to increase community preparedness in facing flood disasters. Optimizing the use of Destana in this study shows that the community plays an active role by utilizing their local knowledge and resources. In addition, the government remains the main actor in implementing disaster preparedness policies. JEL Classification : D78, J24, R58.